To analyze the function \( y = x^2 - 2 \) and its reflection about the origin, let's first find the original function's x-intercepts and then determine the properties of the reflected function.
-
Finding the x-intercepts of \( y = x^2 - 2 \): The x-intercepts occur where \( y = 0 \).
Set the equation equal to zero: \[ x^2 - 2 = 0 \] Solving for \( x \): \[ x^2 = 2 \] \[ x = \pm \sqrt{2} \]
Thus, the function \( y = x^2 - 2 \) has 2 x-intercepts at \( x = \sqrt{2} \) and \( x = -\sqrt{2} \).
-
Reflecting the function about the origin: To reflect a function \( y = f(x) \) about the origin, we transform it to \( y = -f(-x) \).
For our function, this means: \[ y = -(f(-x)) = -((-x)^2 - 2) = -((x^2) - 2) = -x^2 + 2 \]
The reflected function is \( y = -x^2 + 2 \).
-
Finding the x-intercepts of \( y = -x^2 + 2 \): Now, we'll set this equation equal to zero to find its x-intercepts: \[ -x^2 + 2 = 0 \] Rearranging this gives: \[ x^2 = 2 \] \[ x = \pm \sqrt{2} \]
Thus, the reflected function \( y = -x^2 + 2 \) also has 2 x-intercepts at \( x = \sqrt{2} \) and \( x = -\sqrt{2} \).
Conclusion
Since both the original function and the reflected function have 2 x-intercepts, the answer to the question is:
2 x-intercepts.